Norepinephrine in the Medial Pre-frontal Cortex Supports Accumbens Shell Responses to a Novel Palatable Food in Food-Restricted Mice Only - Latagliata, Emanuele Claudio; Puglisi-Allegra, Stefano; Ventura, Rossella; Cabib, Simona (Frontiers in Behavioral Neuroscience, 2018)
Previous findings from this laboratory demonstrate: 1) that different classes of addictive drugs require intact norepinephrine transmission in the medial pre Frontal cortex to promote conditioned place preference and to increase dopamine tone in the nucleus accumbens shell; 2) that only food-restricted mice require intact norepinephrine transmission in the medial pre Frontal cortex to develop conditioned preference for a context associated with milk chocolate; and 3) that food-restricted mice show a significantly larger increase of medial pre Frontal cortex norepinephrine outflow then free fed mice when experiencing the palatable food for the first time. In the present study we tested the hypothesis that only the high levels of frontal cortical norepinephrine elicited by the natural reward in food restricted mice stimulate mesaccumbens dopamine transmission. To this aim we investigated the ability of a first experience with milk chocolate to increase DA outflow in the accumbens Shell and c-fos expression in striatal and limbic areas of food–restricted and ad-libitum fed mice. Moreover, we tested the effects of a selective depletion of frontal cortical norepinephrine on both responses in either feeding group. Only in food-restricted mice milk chocolate induced an increase of dopamine outflow beyond baseline in the accumbens Shell and a c-fos expression larger than that promoted by a novel inedible object in the nucleus accumbens. Moreover, depletion of frontal cortical norepinephrine selectively prevented both the increase of dopamine outflow and the large expression of c-fos promoted by milk chocolate in the Nucleus accumbens Shell of food-restricted mice. These findings support the conclusion that in food-restricted mice a novel palatable food activates the motivational circuit engaged by addictive drugs and support the development of noradrenergic pharmacology of motivational disturbances.